Substrate Uptake and Subcellular Compartmentation of Anoxic Cholesterol Catabolism in Sterolibacterium denitrificans - Lin, Ching-Wen (J Biol Chem, 2015)
Cholesterol catabolism by actinobacteria has been extensively studied. In contrast, the uptake and catabolism of cholesterol by Gram-negative species are poorly understood. Here, we investigated microbial cholesterol catabolism at the subcellular level. (13)C metabolomic analysis revealed that anaerobically grown Sterolibacterium denitrificans, a β-proteobacterium, adopts an oxygenase-independent pathway to degrade cholesterol. S. denitrificans cells did not produce biosurfactants upon growth on cholesterol and exhibited high cell surface hydrophobicity. Moreover, S. denitrificans did not produce extracellular catabolic enzymes to transform cholesterol. Accordingly, S. denitrificans accessed cholesterol by direction adhesion. Cholesterol is imported through the outer membrane via a putative FadL-like transport system, which is induced by neutral sterols. The outer membrane steroid transporter is able to selectively import various C(27) sterols into the periplasm. S. denitrificans spheroplasts exhibited a significantly higher efficiency in cholest-4-en-3-one-26-oic acid uptake than in cholesterol uptake. We separated S. denitrificans proteins into four fractions, namely the outer membrane, periplasm, inner membrane, and cytoplasm, and we observed the individual catabolic reactions within them. Our data indicated that, in the periplasm, various periplasmic and peripheral membrane enzymes transform cholesterol into cholest-4-en-3-one-26-oic acid. The C(27) acidic steroid is then transported into the cytoplasm, in which side-chain degradation and the subsequent sterane cleavage occur. This study sheds light into microbial cholesterol metabolism under anoxic conditions.